The Utilization of Smartphone to Facilitate EFL Learners’ Reading Comprehension Improvement - Annisa Rahim; Sofia Listika; Syania Delila; Vivi Novita (English Instruction, 2020)
The smartphone is a technology that is currently widely used as a medium of learning. Moreover, as a medium to improve reading comprehension skills, the way to use a smartphone, which is mostly by reading, is one way of improvising reading comprehension skills. Because reading is a significant skill that learners should know. There are various types of research on the use of smartphones in improving reading skills. The results show that EFL students prefer reading comprehension via mobile phones because of the convenience facilitated by the portability and accessibility of mobile phones. reading can be the means by which a thing is taken or understood. reading doesn't just mean knowing words or descriptive linguistics. Reading strategies can be classified into four types namely skimming, scanning, extensive and intensive reading.